Temperature dependence of Cu:SnO2 film conductivity in air medium - N.A. Klychkov; V.V. Simakov; I.V. Sinev (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2023)
Temperature conductivity studies of films based on Cu:SnO2 made by magnetron sputtering of the mixed target CuO/SnO2 have been carried out. Temperature conductivity dependencies were substantially nonlinear. It was found that the local conductivity minimum was observed near the temperature of 330°C. To explain the results, a mathematical model is proposed of oxygen adsorption in various forms on the surface of wide-bandgap semiconductors. It was assumed that oxygen particle adsorption resulted in energy levels of the acceptor type localized near the surface of the semiconductor. The simulation carried out within the proposed model showed qualitative and quantitative consistency of the calculation results and experimental data of the temperature dependence of conductivity of the formed gas-sensitive Cu:SnO2 layers in oxygen-containing atmosphere. An analysis of experimental temperature dependence showed that the local conductivity minimum is due to the process of dissociation of oxygen particles adsorbed in molecular form. The desorption energies of each form of adsorbed oxygen and the depth of their surface acceptor level are assessed.